2020
DOI: 10.1017/s0022149x20000917
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive compensation in female Palaemonetes argentinus (Decapoda: Natantia) due to Microphallus szidati (Trematoda) infection

Abstract: Parasites may affect host demographic characteristics because they can directly or indirectly cause the death of their hosts and/or influence their reproduction. Parasitism is therefore recognized as a factor that influences the composition and structure of populations and communities. One of these behaviours is the compensatory response: the host can compensate for the parasite losses effect, modifying the reproductive effort to enhance fitness. Ovigerus female Palaemonetes argentinus was collected and sorted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although it is unknown whether this decrease in spawning is a widespread phenomenon in Chile, its association with the increase in parasite intensity, which according to our results is positively related to the level of progesterone (Figure 6D), suggests a compensatory response of parasitized F. crassa against the oocyte losses during spawning. In this sense, increased fecundity would reflect a trade-off between the number and size of eggs (Einum and Fleming, 2000;Rollingson and Hutchings, 2013), with eggs from infected females having a smaller area, as has been observed in other host-parasite systems (Heins, 2012;Parietti et al, 2020). Previous studies have shown that parasitized limpets F. crassa have more parasite intensity in sites where the GSI is also higher, suggesting that the increase in gonadal biomass could provide more space for the accumulation of metacercariae (Aldana et al, 2014;Aldana et al, 2020;Garcıá-Huidobro et al, 2020).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Although it is unknown whether this decrease in spawning is a widespread phenomenon in Chile, its association with the increase in parasite intensity, which according to our results is positively related to the level of progesterone (Figure 6D), suggests a compensatory response of parasitized F. crassa against the oocyte losses during spawning. In this sense, increased fecundity would reflect a trade-off between the number and size of eggs (Einum and Fleming, 2000;Rollingson and Hutchings, 2013), with eggs from infected females having a smaller area, as has been observed in other host-parasite systems (Heins, 2012;Parietti et al, 2020). Previous studies have shown that parasitized limpets F. crassa have more parasite intensity in sites where the GSI is also higher, suggesting that the increase in gonadal biomass could provide more space for the accumulation of metacercariae (Aldana et al, 2014;Aldana et al, 2020;Garcıá-Huidobro et al, 2020).…”
Section: Discussionmentioning
confidence: 83%
“…The increase in the percentage of reproductively active host females, at low infection levels, was considered as a mechanism that could compensate for the subsequent reduction in snail fecundity, as a result of the increase in trematode intensity (Serbina, 2014). Studies carried out on the shrimp Palaemonetes argentinus, the second intermediate host for the digenean Microphalus szidati, demonstrated that parasitized females produced more embryos, but had more egg loss throughout embryonic development than non-parasitized females (Merlo et al, 2016;Parietti et al, 2020). In this sense, female shrimp should produce a greater number of offspring at the early season to compensate for egg losses as a result of being parasitized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation